Determinants of Investment in Equity Crowdfunding for Micro, Small and Medium Enterprises (UMKM) - Legri Andiani; Titik Mildawati; Maswar Patuh Priyadi (Lead Journal of Economy and Administration, 2025)
This study explores the key factors influencing investor interest in micro, small, and medium enterprises (MSMEs) through equity crowdfunding (ECF) on the Santara platform. It examines the impact of stock price, number of outstanding shares, investment yield, dividend policy, and social media exposure. Using purposive sampling, data were collected from 36 fully funded MSMEs listed as of October 1, 2020, and analyzed using multiple linear regression. The results show that stock price, number of outstanding shares, dividend policy, and social media presence positively affect investor interest, while investment yield has no significant impact. These findings offer insights for MSMEs to better strategize their funding approaches in digital investment platforms.